2008
DOI: 10.1002/lary.20041
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and safety of OK‐432 immunotherapy of lymphatic malformations

Abstract: ClinicalTrials.gov Identifier: NCT00010452.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
121
1
10

Year Published

2010
2010
2019
2019

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 140 publications
(135 citation statements)
references
References 15 publications
2
121
1
10
Order By: Relevance
“…Whereas, in this prospective survey, no microcystic LM responded properly to the sclerotherapy (6). A study with repeated sclerotherapy using bleomycin A5 hydrochloride presented 78.57% effectiveness in a microcystic LM cohort.…”
Section: Introductionmentioning
confidence: 61%
“…Whereas, in this prospective survey, no microcystic LM responded properly to the sclerotherapy (6). A study with repeated sclerotherapy using bleomycin A5 hydrochloride presented 78.57% effectiveness in a microcystic LM cohort.…”
Section: Introductionmentioning
confidence: 61%
“…[12][13][14][15] However, several authors have suggested that sclerotherapy may be a more appropriate first-line therapy. 16,17 Although sclerotherapy is now well established in the treatment of neonatal and paediatric cystic hygromas, there have been relatively few cases reported of its use in adult patients. Some success has been reported in small numbers of adults with sclerotherapy agents such as OK-432.…”
Section: Discussionmentioning
confidence: 99%
“…18 Caution has been urged with the use of agents such as OK-432 which induce a local immune response that often results in a rapid temporary increase in the size of the cystic hygroma. 17,18 Smith et al compared results from their large-scale trial of OK-432 with pooled results from large surgical case series reported in the literature and reported greater success rates and lower occurrence of major complications with OK-432 sclerotherapy compared with surgical excision. 17 In addition, clinical success of OK-432 treatment was defined as a greater than 60% reduction in size.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations